Reflection Of Changes In The Industry Of Surkhandarya Region In The Early Years Of Independence In The Press (Eurasian Journal of Humanities and Social Sciences, 2024)
At a time when the processes of integration of the peoples of the world and globalization in the economy are accelerating, the importance of understanding the ethnic and cultural identity, preserving local ethno-regional cultures and national values is increasing. In particular, the importance of nationality is growing in socio-political processes, attention is paid to the growing interest in their history and traditional culture among the peoples of the world, and research in this direction determines the relevance of the topic.